1989
DOI: 10.1149/1.2096301
|View full text |Cite
|
Sign up to set email alerts
|

The Solubility of NiO in Binary Mixtures of Molten Carbonates

Abstract: The solubility of NiO in mixtures of Li2CO3-K2CO3 and Na2CO~-K2CO3 was measured as a function of the calculated basicity of the solvent mixture and as a function of the temperature. Acid and basic dissolution were found in all mixtures of the Na2CO3-K2CO3 system and in the K2CO3-rich mixtures of the Li2CO3-K2CO3 system. The slopes of the acid solubility lines were markedly different from those in the single salts. The solubilities in mixtures were not quantitatively related in a simple manner to the solubiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 6 publications
3
33
0
Order By: Relevance
“…Several measurements 6,7,10 have shown that the solubility of transition metal oxides (e.g., NiO) is independent of the partial pressure of oxygen. Therefore the involvement of gaseous oxygen, being either produced or consumed during the dissolution of metal oxides, is not considered.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several measurements 6,7,10 have shown that the solubility of transition metal oxides (e.g., NiO) is independent of the partial pressure of oxygen. Therefore the involvement of gaseous oxygen, being either produced or consumed during the dissolution of metal oxides, is not considered.…”
Section: Methodsmentioning
confidence: 99%
“…As Orfield and Shores 3,6 proposed, the formation of complex ions might be one of the explanations. This paper is devoted to an investigation of the solubility of metal oxides from the viewpoint of the complex formation.…”
Section: ϫmentioning
confidence: 98%
See 3 more Smart Citations